Experience of Overcome Nausea and Vomiting in Dengue Fever: A Phenomenology Study - Sumeru, Annas; Sari, Yunita; Taufik, Agis; Mustikasari, Dian (Journal of Bionursing, 2024)
In a tropical country like Indonesia, renowned for its two seasons (rainy and dry season), a transitional period is observed between these seasons, aptly referred to as the transition season. During this transitional phase, the Aedes mosquito rapidly breeds, laying its eggs. Sunlight enhances this process, warming the air and puddles, thereby contributing to the hatching of eggs and potentially causing an endemic outbreak of dengue fever. This study aims to explore the experiences of individuals in overcoming nausea and vomiting during dengue fever. Employing a phenomenological qualitative research design, the research involves 7 participants selected through purposive sampling. The research process includes bracketing, intuition, analysis, and the generation of descriptions and interpretations. Bracketing is undertaken to ensure that the information gathered is genuinely natural and derived from participants' direct expressions regarding their experiences in handling nausea and vomiting during dengue fever. In the intuition stage, the researcher strives to recognize and understand the phenomenon under study. The data is analyzed using qualitative content analysis with the Collaizi approach, involving stages such as reading and re-reading collected data, selecting keywords through coding, categorizing identified keywords, grouping meanings into themes, creating a provisional narrative, validating the narrative with participants, and finally, presenting the validated narrative as the final study output. The research reveals several findings: Nausea and feeling unwell are likened to catching a cold; nausea intensifies in response to specific smells or food aromas; respondents can only consume small portions; and notably, respondents alleviate sickness by drinking warm water. During dengue, feelings of weakness compel participants to maintain an intense but small food intake to sustain energy. Nausea and vomiting experiences are not uniformly perceived as uncomfortable by respondents, and when contemplating the use of warm water to relieve nausea, considerations must be made regarding its safety and potential unknown side effects.